(untitled) (Journal of the College of Basic Education, 2024)
The research aims to: identify the effect of teaching according to situational learning in developing grammatical skills among students of Arabic language departments. For this reason, the researcher derived the following null hypothesis: (There are no statistically significant differences between the grades of the grammatical skills test for members of the experimental group taught according to situational learning, and the grades of the grammatical skills of the members of the control group taught according to the usual method.) The researcher adopted the experimental design with partial control, which is the design of the control and experimental groups with a post-test. The research sample consisted of (32) male and female students from the third stage, Arabic Language Department, with (16) students for the experimental group, and (16) students for the group. The researcher was rewarded. Between the two research groups, in testing prior knowledge in grammar and intelligence testing, the researcher formulated (93) behavioral objectives distributed across the six levels of the cognitive domain of Bloom’s taxonomy (remembering, understanding, applying, analyzing, synthesizing, evaluating). The researcher prepared a grammatical skills test, which consisted of (40) multiple-choice items that measured grammatical skills, and used the Mann-Whitney U test in processing the data, in addition to using statistical methods (difficulty coefficient of thematic paragraphs, coefficient of discrimination power of thematic paragraphs, effectiveness of alternatives). error, the Mann-Whitney effect size for two independent samples, to verify the results, The search results showed the following: _ There are statistically significant differences at the significance level (0.05) between the grade levels of the experimental group students and the grade levels of the control group students, in favor of the experimental group